Bioactive Phytochemicals in Health and Disease - Iriti, Marcello; Martins, Natália; Rodrigues, Célia F. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nutritional deficiencies, and different nutritional and dietary lifestyles, whether poor or absent of essential nutrients, aside from excess intake, can lead to inflammatory complications and loss of function. Bioactive compounds are non-nutritional components derived from plants, foods, and beverages with a multitude of biological effects. The improvement of analytical techniques has allowed scientific community to state that the regular consumption of bioactive phytochemicals is related to the prevention of numerous pathologies, through mechanisms that involve oxidative stress reduction, gene expression modulation, and even enzymatic activation inhibition.